Radiology review manual - Dähnert, Wolfgang (Wolters Kluwer, 2017)
This volume provides information for board exam preparation, teaching, and the daily practice of radiology. Includes extensive lists of image findings and differential diagnoses, an accessible outline format, and a thorough index. Updates to this edition include techniques in nuclear medicine and contrast media, statistics, sedation, analgesia, and local anesthesia.